2004
DOI: 10.1364/opex.12.006540
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing specimen induced aberrations for high NA adaptive optical microscopy

Abstract: Aberrations are known to severely compromise image quality in optical microscopy, especially when high numerical aperture (NA) lenses are used in confocal fluorescence microscopy (CFM) and two-photon microscopy (TPM). The method of adaptive optics may correct aberrations and restore diffraction limited operation. So far the problem of aberrations that occur in the imaging of biological specimens has not been quantified. However, this information is essential for the design of adaptive optics systems. We have t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
90
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 28 publications
1
90
0
1
Order By: Relevance
“…One should therefore expect reduced performance both in terms of transmission and aberrations. Furthermore, aberrations are introduced by the specimens themselves, particularly by thick specimens to which HGM is often applied [5]. As the harmonic generation is nonlinearly dependent on the excitation intensity, these factors could have a significant effect on the imaging performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One should therefore expect reduced performance both in terms of transmission and aberrations. Furthermore, aberrations are introduced by the specimens themselves, particularly by thick specimens to which HGM is often applied [5]. As the harmonic generation is nonlinearly dependent on the excitation intensity, these factors could have a significant effect on the imaging performance.…”
Section: Introductionmentioning
confidence: 99%
“…In early-stage mouse embryos, THG images reveal cellular structure and sub-cellular features, whereas SHG has shown mitotic spindles and the zona pellucida. It has also been shown that large aberrations are induced when focussing through embryos [5]. When combined with the system aberrations arising from the nonoptimal objective lenses, the effects can cause a significant reduction in signal level and resolution.…”
mentioning
confidence: 99%
“…For example, one of the most widely applied microscopy techniques for in vivo imaging, two-photon fluorescence microscopy, often uses water-dipping objectives. Because biological samples are comprised of structures (i.e., proteins, nuclear acids, and lipids) with refractive indices different from that of water, they induce optical aberrations to the incoming excitation wave and result in an enlarged focal spot within the sample and a concomitant deterioration of signal and resolution (2,3). As a result, the resolution and contrast of optical microscopes is compromised in vivo, especially deep in tissue.…”
mentioning
confidence: 99%
“…It is assumed that the wavefront aberration can be represented by a finite low-order Zernike aberrations [13,26,27], then it is possible that the DM can generate these low-order Zernike modes efficiently and Δφ x (ξ , η) can be neglected. As a result, Eq.…”
Section: Modeling Of the Wfsless Ao Systemmentioning
confidence: 99%